Party v. The People: Testing corrective action and supportive engagement in a partisan political context. Issue 3 (3rd July 2019) - Duncan, Megan; Coppini, David
ABSTRACT: Today's audiences have an opportunity to hear the political opinions of a more diverse sample of voters through online comment sections. Two theories suggest that the hostile or supportive climate created by peers will influence the audience's engagement with comment sections. Corrective action hypothesis posits that citizens will engage offline and online when they perceive a hostile opinion climate. Meanwhile, the supportive-based engagement theory suggests that some audience members will be more likely to participate when a homogenous opinion climate speeds opinion crystallization. This study extends the engagement literature to the opinion climate created by online comments by investigating the interaction between political partisanship and the hostility of comments about a political candidate. In a 3 (political party congruence) X 3 (level of comment hostility) controlled experiment ( N = 350), party identification of a candidate and the hostility of comments were manipulated. The change in opinion about the candidate and the likelihood of expressing a public opinion were measured. Results indicate the audience is most likely to express an opinion when the candidate and the audience member share party identification. Further, the study finds an interaction so that hostile opinion climate increased opinion polarization. Results suggest that audiences are more likely to support a fellow partisan being attacked than to attack a member of the political outgroup who is being supported. Finally, it finds the perception that comments will influence others has a role in opinion change and likelihood of expressing an opinion.